Bacterial Infection and Seminal Fluid Parameters in Iraqi Sub Fertile Men - Mamdooh A. Al_ Nasrawi1 , Loqman J. Tawfiq2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Semen samples of 60 sub fertile men that aged from 25 and 45 years that attending an Al-Sammrai infertility hospital from10-10-2017 to 5-12-2018 and were examined for bacteriological culture. The patients divide to negative group (A) the second as positive group (B). Semen were chaked from the groups and analyzed for viscosity, sperm morphology, semen volume, sperm concentration, and motility percent. The results for cultures was negative in 15% and positive in 85% of patients. The isolated organisms were as the following percentage ( Escherichia coli 11%, Staph. aureus (16%), B-hemolytic streptococcus 30%, Staphylococcus epidermidis 43 %). The semen characteristics in infected samples showed that the motility and viability of spermatozoa were lower when compared to noninfected semen sample. That are means, the infections have a direct effect on seminal fluid quality and subsequently negative effects on human fertility. The results showed that there are a highly significant difference (p?0.001) between fertility power in noninfected men and infected cases.